The impact of financial incentives on physical activity for employees in the context of workplace health promotion: a systematic review - Vitzthum, Miriam Alice; Krüger, Karsten; Weyh, Christopher; Justus Liebig University Giessen (My University, 2024)
Objectives: The global increase in physical inactivity is progressively evolving into a significant health challenge. Alongside the promotion of more active leisure pursuits, elevating physical activity in the workplace has come into focus. Financial incentives are not only a popular but also a promising tool in this regard. According to behavioral economics, they are able to initiate physical activity and thus create the basis for behavioral change. Methods: The present systematic review was prepared according to the current PRISMA guidelines and with reference to the Cochrane Handbook. A systematic literature search of 6 electronic databases and 3 study registers was conducted to identify relevant literature. Both randomized controlled trials (RCTs) as well as non-RCTs were included. The Cochrane Risk-of-Bias Tool and the ROBINS-I Tool were used to assess the risk of bias of individual studies, whereas the GRADE approach was used to evaluate the quality of evidence for all studies related to physical activity outcomes. A narrative synthesis was conducted. Results: Six studies were included in the review. Among the total of 2646 participants, the average age ranged from 35.5 to 43.3 years, and women accounted for between 48.6% and 88%. Risk of bias was rated as “high” in 3 studies, “moderate” in 2, and “low” in 1. The quality of evidence was assessed as “moderate.” Four of the 6 studies reported positive effects on physical activity during the incentive period. Conclusions: Workplace health promotion incorporating financial incentives has the potential to positively impact the physical activity levels of employees.
Keywords: ddc:796